2006
DOI: 10.1530/eje.1.02278
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic ACTH syndrome: our experience with 25 cases

Abstract: Objective: Ectopic ACTH syndrome (EAS) occurs in about 5-10% of all patients with ACTH-dependent hypercortisolism with most of them caused by intrathoracic neoplasms. It may be associated with overt malignancies or with occult and indolent tumors. We assessed the accuracy of dynamic tests, inferior petrosal sinus sampling (IPSS) using desmopressin, and imaging in the work-up diagnosis of EAS. Design and subjects: Tumor markers, imaging, and outcome data from 25 patients (13F/12M) aged 18-72 years. High dexamet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
125
1
13

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(151 citation statements)
references
References 62 publications
12
125
1
13
Order By: Relevance
“…The favorable survival rate of BC compared with other ACTH-secreting tumors had already been observed in other studies (6,7,19). Conversely, survival rate of occult tumors in our series was poorer than that of BC and similar to that of pNET, in contrast to the results reported by Ilias et al (6).…”
Section: Discussionsupporting
confidence: 66%
“…The favorable survival rate of BC compared with other ACTH-secreting tumors had already been observed in other studies (6,7,19). Conversely, survival rate of occult tumors in our series was poorer than that of BC and similar to that of pNET, in contrast to the results reported by Ilias et al (6).…”
Section: Discussionsupporting
confidence: 66%
“…high plasma ACTH and serum cortisol levels and a lack of response to CRH, even though the rare EAS patients with mild hypercortisolism can theoretically escape detection from the parameter combinations (12,(23)(24)(25)(26). The characteristics of the hCRH response and the above correlations, reflecting a preserved physiological negative feedback mechanism in CT and PC subjects and its loss in CS patients, have also partially been described.…”
Section: Discussionmentioning
confidence: 99%
“…Salgano et al reported that a high dose of dexamethasone caused a high false-positive rate in lung carcinoid tumors [2]. These results suggest that a high-dose dexamethasone test is also useful for the diagnosis of Cushing's disease, although we have to pay attention to the results produced in macroadenomas with Cushing's disease and in cases of bronchial carcinoids with EAS [14].…”
Section: Bmentioning
confidence: 98%
“…ACTH release would be caused by an abnormal increase in vasopressin type 1b receptors in response to a vasopressin type 2 receptor agonist, DDAVP, on pituitary corticotroph adenoma cells [6], and has been used for the differential diagnosis of ACTH-dependent Cushing's syndrome [7]. Nevertheless, the data in Cushing's disease has been known to overlap with some cases of EAS [2]. In discussing the present diagnostic criteria, we refer to our extensive data.…”
Section: Low-dose Dexamethasone Suppression Test (Dst)mentioning
confidence: 99%
See 1 more Smart Citation